5(6x+7)=-6x-1

Simple and best practice solution for 5(6x+7)=-6x-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(6x+7)=-6x-1 equation:



5(6x+7)=-6x-1
We move all terms to the left:
5(6x+7)-(-6x-1)=0
We multiply parentheses
30x-(-6x-1)+35=0
We get rid of parentheses
30x+6x+1+35=0
We add all the numbers together, and all the variables
36x+36=0
We move all terms containing x to the left, all other terms to the right
36x=-36
x=-36/36
x=-1

See similar equations:

| 5^4{x-9}=3^6{x} | | W/5-w/10=10 | | 7z+1=10+6z | | 3p+3(1-p)=-1(p+2) | | -15-14x=-141 | | y2+12y=−4y | | 8j+2=8+2j | | x/8=1.6 | | 35=7i | | a÷3=9 | | g(6)=36 | | -8x^2+8x+7=9 | | 5b^2-2b-4=-5 | | 3b7=2 | | 84=6x+5x+7 | | a-¼=2½ | | 35=100+x | | -5k^2-4k-6=-7 | | 9+5x=3x+3 | | -9x^2+6x+4=5 | | h/6+1=-3 | | 3x+1+2x=4x-2-7+7 | | 7-4s=-4(s-5)-8 | | 2g-4=24 | | 180-x-40=x | | -1x/3=11 | | r/6=40 | | -5(-3x-3)+5x+4=−1 | | 2(w-7)=18 | | 20=a5a | | 125=5x-10 | | 6(c+4)=6c+10 |

Equations solver categories